Research on the impact of graphene oxide in feed on growth and health parameters in calves - Aulichova, Tereza; Skalickova, Sylvie; Tomas, Kopec; Chilala, Pompido; Horky, Pavel (Frontiers in toxicology, 2025)
Mycotoxins, as feed contaminants, pose serious health risks and cause significant economic losses on farms. The selection of an appropriate and effective adsorbent remains a key challenge for many researchers. Graphene oxide (GO) and its derivatives have garnered interest due to their exceptional physicochemical properties. However, the increasing use of GO necessitates a thorough investigation into its potential toxic impacts on animal and human health, as well as the environment. This study evaluates the effects of GO as a feed additive on calf health. Ten calves (100 ± 6 kg) participated in a 20-day experiment: five in the control group (C) and five in the experimental group (T). The control group (C) received feed without GO, while the experimental group (T) was fed a diet containing 30 g of GO/kg/day. Key parameters evaluated included growth performance, biochemical markers (ALT, AST, ALP), and mineral levels (Ca, P, Mg, K, Na, Cl, Fe, Cu, Zn). The average weight gain was 16.20 ± 0.32 kg in the control group and 15.40 ± 0.26 kg in the GO group, with no statistically significant difference (p > 0.05). Calves fed GO-enriched feed exhibited significant reductions in Fe (p = 0.041) and Zn (p = 0.0006) levels, while Mg increased significantly in the control group (p = 0.029). Liver parameters in group T showed significant increases in ALT (p = 0.022), AST (p = 0.027), and ALP (p = 0.015) after 20 days. Additionally, GPx activity was significantly decreased in the GO group (p = 0.011). These results suggest that GO at a dose of 30 g/kg/day in feed can negatively affect calf health.
Keywords: cattle; toxic; graphene oxide; adsorbent; animal